Cumplicidade - Raimundo, João (2021)
The present work intends to analyze the figure of complicity provided for in article 27 of the Portuguese Penal Code to discuss aspects shed on complicity material and moral (which is the subject of study); analyze their limits in relation to figures of co-authorship and inciting (the specific objective or problem). This study finds your justification in the fact that in specific cases, perhaps by mistake and given your proximity, the conduct of complicity be attributed to co-authorship, the reverse occurs, and also the instigation (before people contest) by the courts. Research methodology: This study will be made on the basis of three concrete cases decided through two judgments of the SUPREME COURT JUSTICE, delivered in case no. 03P3364, on 04.03.2004, Rapporteur: Rodrigues da Costa; in the process paragraph 17/09. OTELSB. L1. S1, 15.12.2011, Rapporteur: Raúl Borges; This contradicted by João Manuel Bellino Athayde Varela, on your doctoral thesis with the title: "the limits of Criminality in the Authorship" (p. 25-29); and a judgment of the Court of Appeal of Port, proc. no. 0412956, 08.02.2006, Rapporteur: Élia São Pedro. Shall be also a conceptual content approach, both of complicity, of co-authorship and instigation, from the concept of "central" by, so as to be able to carry out a critical analysis of Symmetries and/or existing asymmetries between the three figures. Will still be examined issues that have to do with the subjective aspect of complicity (deceit), abetting negligent on the facts, tempted and attempted complicity. Finally, we intend to add suggestions that can help the future task of the ordinary legislator, in criminal matters, with regard to the delimitation of the complicity and the reformulation of your concept.